2010
DOI: 10.1016/j.bbi.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A formal analysis of cytokine networks in Chronic Fatigue Syndrome

Abstract: Chronic Fatigue Syndrome (CFS) is a complex illness affecting 4 million Americans for which no characteristic lesion has been identified. Instead of searching for a deficiency in any single marker, we propose that CFS is associated with a profound imbalance in the regulation of immune function forcing a departure from standard preprogrammed responses. To identify these imbalances we apply network analysis to the co-expression of 16 cytokines in CFS subjects and healthy controls. Concentrations of 1b,2,4,5,6,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
191
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(211 citation statements)
references
References 66 publications
17
191
1
2
Order By: Relevance
“…While there is some evidence that depression is accompanied by an increased production of IFN-γ and a Th1-like response [1,2], most papers show a more prominent Th2 response in ME/CFS [32,33,34,35]. For example, Broderick et al [36] observed suppressed Th1 but increased Th2 responses in ME/CFS, while Nakamura et al [37] found increased IL-10 levels, a Th2-like, anti-inflammatory cytokine, in ME/CFS. The increased neopterin levels established in some ME/CFS patients [16,17,18] and patients suffering from fatigue during chronic Epstein-Barr infections [38] suggest that IFN-γ-induced pathways are activated.…”
Section: Discussionmentioning
confidence: 99%
“…While there is some evidence that depression is accompanied by an increased production of IFN-γ and a Th1-like response [1,2], most papers show a more prominent Th2 response in ME/CFS [32,33,34,35]. For example, Broderick et al [36] observed suppressed Th1 but increased Th2 responses in ME/CFS, while Nakamura et al [37] found increased IL-10 levels, a Th2-like, anti-inflammatory cytokine, in ME/CFS. The increased neopterin levels established in some ME/CFS patients [16,17,18] and patients suffering from fatigue during chronic Epstein-Barr infections [38] suggest that IFN-γ-induced pathways are activated.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated ROS production in CFS patients is sometimes associated with altered innate immunity and an accentuated inflammatory response to exercise [29][30][31][32][33][34][35][36]. However, no clear evidence of a link between abnormal immunity and CFS has been established [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…Negative studies are always problematic because of the possibility of our having found more dramatic effects had we waited longer to sample and prolonged the period of sleep deprivation for another 24 h. Moreover, looking for individual cytokine abnormalities may not reveal discrete abnormalities compared to what using a more integrated network analysis can show (31). However, we designed this study based on the current state of knowledge on the topic by using a maximum exercise demand and overnight sleep deprivation, both of which can make worsen symptoms in CFS patients.…”
Section: Discussionmentioning
confidence: 99%